Autoimmune Encephalitis Misdiagnosis in Adults; A Multicenter Observational Study of Outpatient Subspecialty Clinics. (5th December 2022) - Geschwind, Michael; Lopez-Chiriboga, A. Sebastian; Blackburn, Kyle; Turaga, Sanchit; Binks, Sophie; Zitser, Jennifer; Gelfand, Jeffrey; Day, Gregory; Dunham, Steven; Rodenbeck, Stefanie; Clardy, Stacey; Solomon, Andrew; et al.
Abstract : Objective: To determine the diseases misdiagnosed as AE and potential reasons for misdiagnosis. Background: Misdiagnosis of autoimmune encephalitis (AE) may harm patients. Design/Methods: Patients with AE misdiagnosis were identified (1/1/2014-12/31/2020) from outpatient AE subspecialty clinics including: Mayo Clinic (n = 44); Oxford (n = 18); UT Southwestern (n = 18); UCSF (n = 17); Washington University (n = 6); University of Utah (n = 4). Inclusion criteria were adults (=18 years) with: 1) A prior diagnosis of AE; and 2) An alternative diagnosis made at a participating center. We collected data on clinical features, investigations, fulfillment of possible AE criteria, alternative diagnoses, and potential contributors to misdiagnosis. Results: We identified 107 patients misdiagnosed with AE. Thirty (28%) fulfilled diagnostic criteria for "possible AE". Median onset age was 48 years (inter-quartile range, 35.5-60.5) and 65 (61%) were female. Correct diagnoses included: functional neurologic disorder, 27 (25%); neurodegenerative disease, 22 (21%); primary psychiatric disease, 19 (18%); cognitive deficits from comorbidities, 11 (10%); cerebral neoplasm, 10 (9%); and other, 18 (17%). Onset was insidious (>3 months) in 51 (48%). MRI brain was suggestive of encephalitis in 19/104 (18%) and CSF pleocytosis occurred in 16/84 (19%). Thyroid-peroxidase antibodies were elevated in 24/62 (39%). Positive neural autoantibodies were more frequent in serum (48/105[46%]) than CSF (7/91[8%]; p<0.001) and serum antibodies included: GAD65, 14; voltage-gated-potassium-channel-complex [LGI1, CASPR2 negative], 10; NMDA-receptor by cell-based assay only, 10 (6 negative in CSF); and other, 18. Immunotherapy adverse effects were observed in 17/84 (20%). Potential contributors to misdiagnosis included: over-interpretation of a non-specific positive serum antibody, 53 (50%); misinterpretation of functional, psychiatric, or non-specific cognitive dysfunction as encephalopathy, 41 (38%). Conclusions: Red flags suggesting alternative diagnoses to AE include lack of fulfillment of "possible autoimmune encephalitis" criteria, positive non-specific serum antibody, and insidious onset. Avoiding AE misdiagnosis will prevent morbidity from unnecessary immunotherapies and delayed treatment of the correct diagnosis.